Therapeutic potential of mesenchymal stem cells and stem cell-derived extracellular vesicles in tuberculosis of various localizations: A review - Veronika V. Shumko; Andrei I. Gorelov; Anna N. Remezova; Yanina G. Ivanova; Alexandr N. Muraviov; Natalia M. Yudintceva; Tatiana I. Vinogradova; Anna A. Gorelova (Consilium Medicum)
Experimental and clinical studies using cell therapy are very popular. Mesenchymal stem cells (MSCs) and stem cell-derived extracellular vesicles (EV) are used as one of the components of therapy in these researches. The action of MSCs is mediated by the release of EV which play a direct role in the implementation of several important biological processes: angiogenesis, proliferation, modulation of the inflammatory process and immune response, inhibition of cellular apoptosis, etc. These properties of MSCs and stem cell-derived EV are of interest in the treatment of tuberculosis infection, because an integral part of the pathogenesis of tuberculosis is the creation of specific granulomas and the formation of fibrosis.